OVERVIEW OF THE VALIDATION OF OUT OF WEDDED CHILDREN AS LEGITIMATE CHILDREN (STUDY OF DECISION NUMBER 175/PDT.P/2021/PN ARM) - Rizal, Said; Suhunan Purba, Kevin; Fitriyani Pakpahan, Elvira (Penerbit Lafadz Jaya, 2024)
This research contains a description of the ratification of extra-marital children as legal children. Recognition and ratification of extra-marital children often experience differences in their determination. The research method used by the author in writing this journal is normative legal research method, this legal research examines document studies using various secondary data, such as laws and regulations, court decisions, legal theories and opinions of scientists. Based on the results of the research, the Marriage Law does not regulate the recognition and validation of children, the Civil Code regulates recognition and validation while the Constitutional Court only focuses on the biological relationship between the child and the father. In the Determination of the Airmadidi District Court Number 175/Pdt.P/2021/PN Arm, the judge only looks at positive law without considering other aspects in the ratification of extra-marital children. This research is expected to contribute to the development of science, the author's achievement from this research is to produce scientific works in the form of theses, research journals, and as reference material for other writers in the future.